Biological properties of Vibrio parahaemolyticus lytic phages and transcriptome analysis of their interactions with the host - Duanduan Chen; Zhiwei Wang; Xiangkai Li; Hongchi Du; Kaisheng Zhang; Shengliang Cao; Jianbiao Lu; Shuang Zhao; Hui Wang; Yubao Li (Aquaculture Reports)
Vibrio parahaemolyticus (V. parahaemolyticus) is an opportunistic pathogen primarily affecting aquaculture animals, leading to severe aquatic animal diseases and fatalities. Furthermore, the consumption of undercooked seafood contaminated with this strain can lead to acute gastroenteritis in humans. Bacteriophages are considered as potential antibiotic alternatives that could effectively mitigate the harmful impacts of Vibrio. The complex relationship between phages and their hosts is still not fully understood. By exploring the fundamental biological characteristics of phages and the transcription of host mRNA during interactions with their hosts, we can systematically investigate the regulatory networks that govern the function of host molecules produced by both phages and bacteria. We isolated a lytic V. parahaemolyticus phage, vB-VpaS-SD15 (P15), from a shrimp culture pond. Transmission electron microscopy revealed that P15 is a member of the Siphoviridae family of tailed phages. The host spectrum of 138 V. parahaemolyticus strains isolated from aquaculture ponds in the southeastern coast of China was evaluated, indicating that this phage strain could lyse 33 V. parahaemolyticus strains efficiently within a a brief culture period. Furthermore, it exhibited prolonged stability at temperatures up to 60°C, a broad pH range from 2 to 12, diverse forms, and an infection multiplier of 0.01, and the burst volume is about 23 PFU/mL. We completed an interaction map of the host bacterial and phage gene frameworks. Host bacteria were collected at different time points (5 min, 20 min, 40 min, 60 min, 100 min) representing incubation, burst, and plateau phases of phage infection, and were depicted as one-step growth curves. RNA-seq technology was utilized to monitor changes in host bacterial mRNA transcription throughout phage infection. The results suggest that parasitic infection leads to alterations in host genes responsible for various cellular processes like ribosome biogenesis, tRNA biogenesis, secretion, protein export via ABC transporters, TCA cycle, glycolysis/uronic acid production, oxidative phosphorylation, and aminoacyl-tRNA biosynthesis. Notably, genes involved in signaling pathways, such as ribosomal protein genes and multiple antibiotic resistance regulator (MarR) genes, showed significant changes. However, no notable changes were observed in genes associated with the host bacterial classical immune defense system, like the CRISPR system, during the observed time period. These findings offer valuable insights into the alterations in host genes during phage infection, shedding light on the regulatory mechanisms governing the interaction between phages and their hosts. This study lays the groundwork for the potential application of phages in aquaculture production.